The Decision-Making Process for Developing Sustainable Innovation via Dynamic Capabilities in Cleantechs - Eurico Soares de Noronha, Matheus; Maynne Juliano Ferraro, Diandra; de Souza Vieira Silva, Rosemeire (Organizações & Sociedade, 2023)
This article aims to present a model of how the decision-making process can drive the development of dynamic capabilities for generating sustainable innovation in cleantech companies. Cleantechs are highly technological organizations, one of whose main characteristics is little or no use of nonrenewable resources to produce any type of product, service, or process. The use of these technologies and identification of opportunities in the market makes sustainable innovation the core competence of this type of company. A multiple case study was conducted with cleantechs using a qualitative approach, supported by the content analysis technique. The primary data collection was carried out via semi-structured interviews, between October of 2020 and December of 2021, using an interview script as a collection instrument. The results provide a model that illustrates how the decision-making process can drive the development of dynamic capabilities for generating sustainable innovations, by means of categories that reflect technological sustainability, spillover effects, and a drive toward digitalization in clean technologies. The scientific contribution of the study is the presentation of how organizations can restructure their business models and develop sustainable and technological innovations, digitally leapfrogging to address bottlenecks related to energy rationing, social inclusion through monitoring technologies, access to low-cost clean and renewable energy, and other solutions.